Cr-V system out-of-plane ordered double-transition metal MAX phase material and preparation method thereof

By mixing Cr2AlC powder with VC powder, cold press forming and heating and calcining, a high-purity Cr-V system off-plane order double transition metal MAX phase material was successfully prepared, which solved the problem of single MAX phase material synthesis method in the prior art, and achieved the development of the preparation and application of high-purity materials.

CN119503804APending Publication Date: 2025-02-25XI AN JIAOTONG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411703823.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing MAX phase material synthesis method is relatively single, and it is difficult to obtain high-purity off-plane ordered double transition metal MAX phase materials.

Method used

By mixing and grinding Cr2AlC powder with VC powder, cold pressing molding, and heating and calcining treatment in a flowing argon atmosphere, a Cr-V system off-plane order double transition metal MAX phase material was prepared.

Benefits of technology

High purity preparation of Cr2VAlC2 and Cr2V2AlC3 was achieved, with mass fractions reaching 74.9% and 90.1% respectively, expanding the research and application space of MAX phase materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119503804A_ABST
    Figure CN119503804A_ABST
Patent Text Reader

Abstract

The invention discloses a Cr-V system out-of-plane ordered double transition metal MAX phase material and a preparation method thereof, and belongs to the technical field of MAX phase materials.The preparation method comprises the steps that Cr2AlC powder and VC powder are mixed and ground to obtain mixed slurry, the mixed slurry is dried to obtain mixed powder, the mixed powder is subjected to cold press molding and then heated and calcined, and after the mixed powder is cooled to the room temperature, the Cr-V system out-of-plane ordered double transition metal MAX phase material is obtained; the Cr-V system out-of-plane ordered double-transition metal MAX phase material is obtained; the chemical formula of the Cr-V system out-of-plane ordered double transition metal MAX phase material is Cr2VAlC2 or Cr2V2AlC3, and the chemical formula of the Cr-V system out-of-plane ordered double transition metal MAX The mass fraction of the obtained Cr2VAlC2 is 74.9%, and the mass fraction of the obtained Cr2V2AlC3 is 90.1%. And the high-purity Cr2V2AlC3 material with the single MAX phase is prepared for the first time. The material can be further applied to the fields of electromagnetic wave absorption, electric contactors and the like, in the future, the two-dimensional out-of-plane ordered double-transition metal MXene material Cr2V2C3 can be further prepared through etching, and the application of the material in the related fields of energy storage, catalysis and the like is explored.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of MAX phase material preparation, and specifically relates to a Cr-V series out-of-plane ordered double transition metal MAX phase material and a preparation method thereof. Background Art

[0002] MAX phase materials are a large class of nano-layered compounds with a hexagonal structure, and their general formula is M n+1 AX n , where M is mainly a pre-transition metal, A is an A-group element, X represents carbon or (and) nitrogen, and n is generally in the range of 1-3. This type of material has a unique nano-layered crystal structure, in which the M atoms and X atoms are bonded by MX strong covalent bonds, forming an M with a rock salt-like covalent structure. 6 X octahedron, and the M atomic layer and the A layer atoms are bonded by weak MA metal covalent bonds. This unique structure enables the MAX phase to have excellent ceramic and metal properties, including high elastic modulus, acid and alkali corrosion resistance, high temperature oxidation resistance, thermal stability, and excellent electrical conductivity and thermal conductivity. Based on these unique properties, MAX phase materials have extremely high application value in the fields of electrical contactors, sensors, electromagnetic wave absorption, protective coatings, and high-temperature structural materials. In addition, the MAX phase can also be used as a precursor to prepare new transition metal carbon (nitride) two-dimensional materials for applications in electrochemical catalysis, energy storage, electromagnetic shielding, and other fields.

[0003] The remarkable research potential of MAX phase lies in its unique structural design space and the controllable physical and chemical properties such as conductivity and oxidation resistance. Not only can the thickness of different MX layers be obtained by changing the structural properties (the size of n), but also multiple transition metal elements can be doped at the M position and their molar ratio can be adjusted on the basis of retaining the original structure to form a double transition metal or even high entropy MAX phase. Among them, the double transition metal MAX (Out-of-plane Ordered MAX Phase or o-MAX) material with an out-of-plane ordered (interlayer ordered) configuration shows a more special research value due to its unique ordered configuration. The two transition metals in its structure occupy different Wyckoff sites, which provides a new idea for the design of the double transition metal MAX phase (quaternary MAX phase) structure. More importantly, the two-dimensional out-of-plane ordered double transition metal MXene (o-MXene) material obtained by etching the o-MAX phase as a precursor can exhibit a strong spin-orbit coupling effect when containing 4d or 5d heavy transition metals, and thus exhibit some exotic topological properties in the electronic energy band. In addition, studies have also shown that o-MXene can exhibit higher conductivity, more complex metal electronic state changes, and more significant pseudocapacitive charge storage and catalytic activity compared to conventional MXene.

[0004] Based on the above, the exploration of the synthesis of new out-of-plane ordered double transition metal MAX phases has attracted keen attention worldwide. Although theoretical calculations have predicted the existence of dozens of thermodynamically stable o-MAX phases, due to the limitation of the single preparation method, only eight structures have been successfully synthesized and analyzed in experiments so far: Cr 2 TiAlC 2 、Mo 2 TiAlC 2 、Mo 2 SCa 2 、Mo 2 VtC 2 Cr 2 VtC 2 、Mo 2 Ti 2 AlC 3 Cr 2 V 2 AlC 3 and Mo 2 Nb 2 AlC 3 . And among them Cr 2 VtC 2 With Cr 2 V 2 AlC 3 It exists in the form of a mixed phase, and the preparation of a single high-purity MAX phase has not been achieved. The traditional single-element powder metallurgy method is difficult to avoid the competitive phase reaction during the reaction process, and it is impossible to directly obtain a high-purity MAX phase, which greatly limits the research and application exploration of the basic properties of the o-MAX phase. Summary of the invention

[0005] In order to overcome the shortcomings of the above-mentioned prior art, the purpose of the present invention is to provide a Cr-V series out-of-plane ordered double transition metal MAX phase material and a preparation method thereof, so as to solve the technical problem that the existing o-MAX material synthesis method is relatively single and cannot obtain a single and high-purity MAX phase.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions: The present invention discloses a method for preparing a Cr-V series out-of-plane ordered double transition metal MAX phase material, comprising the following steps: Cr 2 AlC powder and VC powder are mixed and ground to obtain a mixed slurry, which is dried to obtain a mixed powder, which is cold pressed and then calcined at a high temperature, and then cooled to room temperature to obtain a Cr-V system out-of-plane ordered double transition metal MAX phase material; The chemical formula of the Cr-V system out-of-plane ordered double transition metal MAX phase material is Cr2 VtC 2 or Cr 2 V 2 AlC 3 .

[0007] Preferably, Cr 2 The molar ratio of AlC powder to VC powder is 1:(0.9~2.0).

[0008] Preferably, Cr 2 The particle size of AlC powder is 100-300 mesh, and the purity is higher than 98%; the particle size of VC powder is 1-10μm, and the purity is higher than 99%.

[0009] Preferably, the grinding method is ball milling, and agate balls and anhydrous ethanol are used as ball milling media during the grinding process; the rotation speed of the ball milling treatment is 120-200 r / min, and the time is 2-6h.

[0010] Preferably, the drying condition is: vacuum rotary evaporation at 40-60°C until completely dry.

[0011] Preferably, the cold pressing forming conditions are: cold pressing at a pressure of 200-500 MPa for 1-3 min to form a round tablet.

[0012] Preferably, the temperature-raising calcination treatment condition is to raise the temperature to 1350-1550° C. at a heating rate of 5-10° C. / min in a flowing argon atmosphere and then keep the temperature for 1-3 hours.

[0013] Preferably, the cooling condition is: cooling to 400-600° C. within 200 min by program-controlled cooling, and then naturally cooling to room temperature.

[0014] The present invention also discloses a Cr-V system out-of-plane ordered double transition metal MAX phase material prepared by the above preparation method. 2 The molar ratio of AlC powder to VC powder is 1:1.2. When the calcination temperature is 1500℃, the chemical formula of the Cr-V system out-of-plane ordered double transition metal MAX phase material is: Cr 2 VtC 2 , the product mass fraction is 74.9%.

[0015] The present invention also discloses a Cr-V system out-of-plane ordered double transition metal MAX phase material prepared by the above preparation method. 2 The molar ratio of AlC powder to VC powder is 1:1.9. When the calcination temperature is 1450℃, the chemical formula of the Cr-V system out-of-plane ordered double transition metal MAX phase material is: Cr 2 V 2 AlC 3, the product mass fraction is 90.1%.

[0016] Compared with the prior art, the present invention has the following beneficial effects: The present invention discloses a method for preparing a Cr-V series out-of-plane ordered double transition metal MAX phase material. The current synthesis method of o-MAX material is relatively single, and the Cr 2 V 2 AlC 3 The present invention provides a novel preparation method to obtain Cr 2 VtC 2 With Cr 2 V 2 AlC 3 The mass fractions reached 74.9% and 90.1% respectively. This invention provides a new idea for the expansion of the synthesis method of out-of-plane ordered double transition metal MAX phase, and opens up a larger space for its basic property research and application exploration. The raw materials and equipment required for preparation are simple and easy to obtain, the purity of the obtained product is considerable, and for the first time, high-purity and single MAX phase Cr 2 V 2 AlC 3 Materials directly expand the relevant research content in this field. 2 The target material is obtained by mixing AlC powder and VC powder, ball milling, tableting and high-temperature sintering. Compared with other laboratory spark plasma sintering or hot pressing sintering processes, this preparation method is simple, efficient and low-cost, and can be further scaled for industrial production. 2 V 2 AlC 3 It can be further used in electromagnetic wave absorption, electrical contactor and other fields. In the future, two-dimensional out-of-plane ordered double transition metal MXene material Cr can be further prepared by etching. 2 V 2 C 3 And explore its application in related fields such as energy storage and catalysis. In addition, the present invention provides a new preparation idea for the development of new o-MAX materials. The experimental idea of ​​preparing high-order MAX phases from low-order MAX through solid-phase reaction can be extended to the development and preparation of more MAX materials.

[0017] Furthermore, adding wet grinding media during the ball milling process can better disperse the materials and improve the fineness and uniformity of the mixed powder. The wet grinding media should be volatile, not react with the powder or dissolve the powder, and be easy to separate later; the amount of wet grinding media added should be moderate, too little or too much is not conducive to the uniform mixing of the raw materials, generally make the anhydrous ethanol just cover the ball; the ball mill speed is 120-200r / min, the coarse powder is easy to settle when the speed is too low, and the slurry will be raised due to centrifugal force when the speed is too high, which is not conducive to the uniform mixing of the raw materials; the ball milling time is 2-6h to obtain a uniform mixture, and too long ball milling time will lead to Cr 2 If AlC is too fine, it will decompose during the sintering process, reducing the yield.

[0018] Furthermore, the temperature rising calcination process is a solid phase reaction of the raw materials, a process for synthesizing o-MAX, and the temperature is raised to the target sintering temperature of 1350-1550°C at a heating rate of 5-10°C / min and then kept warm for 1-3h; the appropriate heating rate, target temperature and holding time are conducive to the formation of the target phase and reduce impurities, thereby improving the final yield.

[0019] The present invention also discloses a Cr-V system out-of-plane ordered double transition metal MAX phase material prepared by the above preparation method, Cr 2 VtC 2 With Cr 2 V 2 AlC 3 , (can also be expressed as (Cr 0.5 V 0.5 ) 4 AlC 3 and (Cr 2 / 3 V 1 / 3 ) 3 AlC 2 ) The Cr prepared by the present invention 2 VtC 2 With Cr 2 V 2 AlC 3 The structure of the out-of-plane ordered double transition metal MAX phase material is the same as that of the existing single-element powder metallurgy method. Specifically, the Cr atoms and V atoms in the crystal structure respectively occupy the outer M position and the inner M position in the MX structure in a highly orderly manner. This order is not absolute, but a spontaneous ordering trend. The Cr 2 V 2 AlC 3 The preparation of single MAX phase lays the foundation for in-depth study of its basic properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 is the Cr in the product of Example 1 2 VtC2 With Cr 2 V 2 AlC 3 Quality score results; Figure 2 is the Cr in the product of Example 2 2 VtC 2 With Cr 2 V 2 AlC 3 Quality score results; Figure 3 In Example 2, Cr 2 The molar ratio of AlC powder to VC powder is 1:1.2. When the calcination temperature is 1500℃, the Cr 2 VtC 2 XRD test and Rietveld refinement spectrum of MAX phase; Figure 4 In Example 1, Cr 2 The molar ratio of AlC powder to VC powder is 1:1.9. When the calcination temperature is 1450℃, the Cr 2 V 2 AlC 3 XRD test and Rietveld refinement spectrum of MAX phase; Figure 5 In Example 2, Cr 2 The molar ratio of AlC powder to VC powder is 1:1.2. When the calcination temperature is 1500℃, the Cr 2 VtC 2 Scanning electron microscope image of MAX phase; Figure 6 In Example 1, Cr 2 The molar ratio of AlC powder to VC powder is 1:1.9. When the calcination temperature is 1450℃, the Cr 2 V 2 AlC 3 Scanning electron microscope image of MAX phase; Figure 7 In Example 2, Cr 2 The molar ratio of AlC powder to VC powder is 1:1.2. When the calcination temperature is 1500℃, the Cr 2 VtC 2 Scanning transmission electron microscopy images, theoretical structures, and element distribution images of MAX phases; Figure 8 In Example 1, Cr 2 The molar ratio of AlC powder to VC powder is 1:1.9. When the calcination temperature is 1450℃, the Cr 2V 2 AlC 3 Scanning transmission electron microscope image, theoretical structure and element distribution image of MAX phase. DETAILED DESCRIPTION

[0021] In order to enable those skilled in the art to better understand the scheme of the present invention, the technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0022] It should be noted that the terms "first", "second", etc. in the specification and claims of the present invention and the above-mentioned drawings are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the data used in this way can be interchanged where appropriate, so that the embodiments of the present invention described herein can be implemented in an order other than those illustrated or described herein. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions, for example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units that are clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices.

[0023] The present invention is further described in detail below in conjunction with the accompanying drawings: The first object of the present invention is to protect two Cr-V system out-of-plane ordered double transition metal MAX phase materials prepared by a new method, the chemical formula of which is: Cr 2 VtC 2 With Cr 2 V 2 AlC 3 , which can also be expressed as (Cr 2 / 3 V 1 / 3 ) 3 AlC 2 and (Cr 0.5 V 0.5 ) 4 AlC 3 .

[0024] The second object of the present invention is to protect a novel preparation method of a Cr-V system out-of-plane ordered double transition metal MAX phase material, comprising the following steps: (1) Weigh Cr in a molar ratio of 1:(0.9~2.0) 2 AlC powder and VC powder; (2) Preparation of Cr-V out-of-plane ordered double transition metal MAX phase materials: The weighed raw materials are ground to obtain mixed powders, the mixed powders are cold pressed, and then calcined at elevated temperatures. After cooling to room temperature, out-of-plane ordered double transition metal MAX phase Cr is obtained. 2 VtC 2 With Cr 2 V 2 AlC 3 .

[0025] Preferably, the molar ratio is 1:1.2 is Cr 2 VtC 2 The optimal process parameters are as follows; the molar ratio of 1:1.9 is Cr 2 V 2 AlC 3 optimal process parameters.

[0026] Preferably, the element powder specifications in step (1) are as follows: Cr 2 AlC is made by mixing Cr powder, Al powder and graphite powder and then sintering. 2 The particle size of AlC powder is 100-300 mesh and the purity is higher than 98%; the particle size of VC powder is 1-10μm and the purity is higher than 99%.

[0027] Preferably, the grinding in step (2) is performed by ball milling, and agate balls and anhydrous ethanol are used as ball milling media during the grinding process. The speed of the ball milling treatment is 120-200 r / min, and the time is 2-6 h. The mixed slurry is vacuum-rotated at 40-60° C. until it is completely dried to obtain a uniformly mixed raw material powder.

[0028] Preferably, the tableting method in step (2) is: cold-pressing the element powder mixture after sufficient ball milling and drying at a pressure of 200-500 MPa for 1-3 minutes into a "round cake" shape.

[0029] Preferably, the method of heating up the calcination and cooling down to room temperature in step (2) is as follows: first, in a flowing argon atmosphere, the temperature is raised to the target sintering temperature of 1350-1550°C at a heating rate of 5-10°C / min, and then kept at that temperature for 1-3h; after the end of the heat preservation, the temperature in the furnace is first reduced to 400-600°C within 200min by means of program-controlled cooling, and sampling is taken after the furnace body is naturally cooled.

[0030] Example 1 A method for preparing a Cr-V system out-of-plane ordered double transition metal MAX phase material comprises the following steps: Accurately weigh Cr 2The molar ratio of AlC powder to VC powder is 1:(0.9-2.0) for multiple groups of raw materials, with an interval of 0.1 between each group, for a total of 12 groups; namely 1:0.9, 1:1.0, 1:1.1, 1:1.2, 1:1.3, 1:1.4, 1:1.5, 1:1.6, 1:1.7, 1:1.8, 1:1.9 and 1:2.0.

[0031] Cr 2 The purity of AlC powder is 98%, and it is pre-sieved with 200 mesh; the purity of VC powder is 99.9%, and the particle size is 1.5μm. The weighed element powder is placed in an agate ball mill, and anhydrous ethanol is added to grind agate balls as wet grinding media. The ball mill is milled at a speed of 140rpm for 2h. The mixed slurry is vacuum-rotated and dried at 50℃ for 1h to obtain a uniformly mixed mixed powder; the raw materials are pressed into discs by using a tablet press at a pressure of about 380MPa for 1min, and placed in a conventional high-temperature tube furnace. The temperature is raised to the target sintering temperature of 1450℃ at a heating rate of 10℃ / min in a flowing argon atmosphere, and then kept warm for 2h; after the insulation is completed, the temperature in the furnace is first reduced to 500℃ within 200min by program-controlled cooling, and then naturally cooled to room temperature to obtain the product.

[0032] Example 2 A method for preparing a Cr-V system out-of-plane ordered double transition metal MAX phase material comprises the following steps: Accurately weigh Cr 2 The molar ratio of AlC powder to VC powder is 1:(0.9-2.0) for multiple groups of raw materials, with an interval of 0.1 between each group, for a total of 12 groups; namely 1:0.9, 1:1.0, 1:1.1, 1:1.2, 1:1.3, 1:1.4, 1:1.5, 1:1.6, 1:1.7, 1:1.8, 1:1.9 and 1:2.0.

[0033] Cr 2 The purity of AlC powder is 98%, which is pre-sieved with 200 mesh; the purity of VC powder is 99.9%, and the particle size is 1.5μm. The weighed element powder is placed in an agate ball mill, and anhydrous ethanol is added to grind agate balls as wet grinding media. The ball mill is milled at a speed of 140rpm for 2h. The mixed slurry is vacuum-rotated and dried at 50℃ for 1h to obtain a uniformly mixed mixed powder; the raw materials are pressed into discs by using a tablet press at a pressure of about 380MPa for 1min, and placed in a conventional high-temperature tube furnace. The temperature is raised to the target sintering temperature of 1500℃ at a heating rate of 10℃ / min in a flowing argon atmosphere, and then kept warm for 2h; after the insulation is completed, the temperature in the furnace is first reduced to 500℃ within 200min by program-controlled cooling, and then naturally cooled to room temperature to obtain the product.

[0034] Cr 2 VtC2 With Cr 2 V 2 AlC 3 All by Cr 2 AlC powder and VC powder are prepared by solid phase reaction. Different raw material molar ratios and different sintering temperatures will produce different phase types and purities. In this example, statistical comparisons were made on the sintering results at different VC powder ratios and target temperatures to optimize the method for preparing Cr 2 VtC 2 With Cr 2 V 2 AlC 3 Process parameters corresponding to the highest mass fraction.

[0035] Product performance test (1) Mass fraction analysis of the prepared product: Figure 1 is the Cr in the product of Example 1 2 VtC 2 With Cr 2 V 2 AlC 3 Quality score results; Figure 2 is the Cr in the product of Example 2 2 VtC 2 With Cr 2 V 2 AlC 3 Mass fraction results; After XRD analysis of the products prepared by the above different raw material VC powder molar ratios and sintering temperatures, the target phase ratio in the product was determined according to the refinement results. The sintering results at 1450℃ and 1500℃ were as follows: Figure 1 and Figure 2 As shown in the results, it was found that with the increase of VC powder molar ratio, the obtained product gradually changed from Cr 2 VtC 2 To Cr 2 V 2 AlC 3 During the sintering process, the two phases compete with each other, accompanied by some Cr 2 AlC or other intermediate phase decomposition products exist, so the optimal raw material ratio is not the theoretical 1:1 and 1:2. According to the quality analysis results, Cr 2 VtC 2 The optimal process parameters are 1.2 parts VC (relative to Cr 2 AlC), sintered at 1500℃, the product mass fraction is 74.9%; while Cr 2 V 2 AlC 3The best process parameters are 1.9 parts VC, sintering at 1450℃, and the product mass fraction is 90.1%.

[0036] (2) The prepared Cr 2 VtC 2 With Cr 2 V 2 AlC 3 The product was characterized by XRD analysis: Figure 3 In Example 2, Cr 2 The molar ratio of AlC powder to VC powder is 1:1.2. When the calcination temperature is 1500℃, the Cr 2 VtC 2 XRD test and Rietveld refinement spectrum of MAX phase; Figure 4 In Example 1, Cr 2 The molar ratio of AlC powder to VC powder is 1:1.9. When the calcination temperature is 1450℃, the Cr 2 V 2 AlC 3 XRD test and Rietveld refinement spectrum of MAX phase; Cr prepared after the above-mentioned optimal process parameters 2 VtC 2 With Cr 2 V 2 AlC 3 X-ray diffraction analysis was performed, and the results were refined by Rietveld to determine the phase type, crystal structure parameters and mass fraction. The results are as follows: Figure 3 and Figure 4 The black line below the picture is the difference between the experimental measurement data and the refined fitting data. The error value R wp The vertical lines of different colors correspond to the theoretical Bragg peak positions of different phases in the sintered product. According to the results of refinement, the Cr prepared in this example 2 VtC 2 The lattice constants of Cr are a=2.887Å, c=17.688Å; 2 V 2 AlC 3 The lattice constants of Cr-V o-MAX materials prepared by powder metallurgy are a=2.910Å and c=22.408Å, which are consistent with the lattice constants of Cr-V o-MAX materials prepared by powder metallurgy reported in the literature, indicating the effectiveness of the MAX materials obtained in the present invention. 2 VtC 2 The impurity phases and their mass fractions are Cr 2 V 2 AlC3 (1.21%), Cr 2 AlC (3.11%), (Cr, V) 3 C 2 (14.99%)、Al 2 O 3 (3.99%)、(Cr,V)C(1.00%) and Cr 7 C 3 (0.78%);Cr 2 V 2 AlC 3 The impurity phases and their mass fractions are (Cr, V) 3 C 2 (2.72%)、Al 2 O 3 (2.02%)、(Cr,V)C(4.52%) and Cr 7 C 3 (0.63%). 2 V 2 AlC 3 The highest mass fraction of the existing single-element metallurgical method is 80.3%, and there are other MAX phases. The Cr prepared in the present invention 2 V 2 AlC 3 A high-purity phase of 90.1% was achieved without any other MAX phases.

[0037] (3) The prepared Cr 2 VtC 2 With Cr 2 V 2 AlC 3 Microscopic morphology and elemental analysis of the product: Figure 5 In Example 2, Cr 2 The molar ratio of AlC powder to VC powder is 1:1.2. When the calcination temperature is 1500℃, the Cr 2 VtC 2 Scanning electron microscope image of MAX phase; Figure 6 In Example 1, Cr 2 The molar ratio of AlC powder to VC powder is 1:1.9. When the calcination temperature is 1450℃, the Cr 2 V 2 AlC 3 Scanning electron microscope image of MAX phase; Scanning electron microscope (SEM) was used to analyze the Cr prepared after the above-mentioned optimal process parameters. 2 VtC 2 With Cr 2 V2 AlC 3 The microstructure analysis was carried out and the results were as follows Figure 5 and Figure 6 The particles in the image have clear structures and distinct boundaries, showing the typical layered structure characteristics of MAX materials. The particles have good crystallinity, and the crystal diameter reaches more than ten microns, indicating the high quality of the Cr-V o-MAX materials prepared by the present invention. The elemental analysis of the samples found that the stoichiometric ratio between Cr and V is not fixed. 2 VtC 2 With Cr 2 V 2 AlC 3 The theoretical Cr-V ratio should be 2:1 and 1:1. The measured value fluctuates around the theoretical value. This is a normal phenomenon in o-MAX materials. The same is true for the ratios of Al and C elements. The slight difference in the stoichiometric ratio should not be used as a criterion for determining a new phase. In this embodiment, the Cr-V stoichiometric ratio in the reactants was adjusted to 2:1.2 and 2:1.9, which is the result of the optimal mass fraction of the target product obtained from experimental measurements. The purpose is to promote the reaction and reduce the generation of competitive phases and impurities. However, it is still believed that the obtained results can be marked according to the theoretical values ​​of o-MAX.

[0038] (4) The prepared Cr 2 VtC 2 With Cr 2 V 2 AlC 3 The products were analyzed by scanning transmission electron microscopy: Figure 7 In Example 2, Cr 2 The molar ratio of AlC powder to VC powder is 1:1.2. When the calcination temperature is 1500℃, the Cr 2 VtC 2 Scanning transmission electron microscopy images, theoretical structures, and element distribution images of MAX phases; Figure 8 In Example 1, Cr 2 The molar ratio of AlC powder to VC powder is 1:1.9. When the calcination temperature is 1450℃, the Cr 2 V 2 AlC 3 Scanning transmission electron microscopy images, theoretical structures and element distribution images of MAX phase; high-angle annular dark field (HAADF) imaging of the prepared Cr using scanning transmission electron microscopy (STEM) 2 VtC 2 With Cr 2 V 2 AlC 3Atomic arrangement analysis and element distribution characterization were performed, and the results were as follows: Figure 7 and Figure 8 As shown. The brighter dots in the image are transition metals, the darker dots in the middle are Al atoms, and C atoms are not visible in the HAADF mode. The images show Cr 2 VtC 2 The three-layer M atomic structure in the crystal and the Cr 2 V 2 AlC 3 The four-layer M atomic structure in the crystal, the lattice constant measured by STEM image is consistent with the XRD refinement result. The ideal crystal structure of two o-MAX structures of Cr-V series is shown on the left side of the image, which is in good agreement with the STEM image. High-resolution elemental distribution characterization (EDS) confirmed the preparation of Cr 2 VtC 2 With Cr 2 V 2 AlC 3 The orderliness of the arrangement of transition metal atoms, such as Figure 7 and Figure 8 As shown on the right, V atoms (yellow) are obviously concentrated in the inner M site, while Cr atoms (red) are more distributed in the outer M site. It should also be noted that the distribution of Cr and V is not completely ordered, and the element distribution images show signal dispersion, which indicates that the arrangement of atoms at the M site is not completely ordered like the ideal o-MAX structure. The out-of-plane order of Cr-V expresses a thermodynamically driven order trend, that is, Cr tends to be arranged at the outer M site, and V tends to be arranged at the inner M site. In the actual prepared crystal structure, solid solution between Cr-V atoms will occur at both the inner and outer M sites. This is consistent with the high-resolution neutron diffraction (HR-ND) results of the powder metallurgy method for preparing Cr-V o-MAX materials reported in the literature, so the STEM-EDS results are sufficient to confirm that the Cr prepared in this example 2 VtC 2 With Cr 2 V 2 AlC 3 It is an out-of-plane ordered double transition metal MAX phase.

[0039] Example 3 A method for preparing a Cr-V system out-of-plane ordered double transition metal MAX phase material comprises the following steps: Accurately weigh Cr with a molar ratio of 1:1.9 2 AlC powder and VC powder; Cr 2The purity of AlC powder is 99%, which is pre-sieved with 100 mesh; the purity of VC powder is 99.1%, and the particle size is 10μm. The weighed element powder is placed in an agate ball mill, and anhydrous ethanol is added to grind agate balls as wet grinding media. The ball mill is milled at a speed of 200rpm for 6h. The mixed slurry is vacuum-rotated at 60℃ until it is completely dried to obtain a uniformly mixed mixed powder; the raw materials are pressed into discs by using a tablet press at a pressure of about 200MPa for 3min, and placed in a conventional high-temperature tube furnace. The temperature is raised to the target sintering temperature of 1350℃ at a heating rate of 5℃ / min in a flowing argon atmosphere, and then kept warm for 3h; after the insulation is completed, the temperature in the furnace is first reduced to 600℃ within 200min by program-controlled cooling, and then naturally cooled to room temperature to obtain the product.

[0040] Example 4 A method for preparing a Cr-V system out-of-plane ordered double transition metal MAX phase material comprises the following steps: Accurately weigh Cr with a molar ratio of 1:1.2 2 AlC powder and VC powder; Cr 2 The purity of AlC powder is 98.5%, which was pre-sieved with 300 mesh; the purity of VC powder is 99.5%, and the particle size is 1μm. The weighed element powders were placed in an agate ball mill, and anhydrous ethanol was added to grind agate balls as wet grinding media. The mixture was ball milled at 120rpm for 2h. The mixed slurry was vacuum-rotated at 40℃ until completely dry to obtain a uniformly mixed powder. The raw materials were pressed into discs by using a tablet press at a pressure of about 500MPa for 3min, and placed in a conventional high-temperature tube furnace. The temperature was raised to the target sintering temperature of 1550℃ at a heating rate of 10℃ / min in a flowing argon atmosphere, and then kept warm for 1h. After the insulation, the temperature in the furnace was first reduced to 400℃ within 200min by program-controlled cooling, and then naturally cooled to room temperature to obtain the product.

[0041] Example 5 A method for preparing a Cr-V system out-of-plane ordered double transition metal MAX phase material comprises the following steps: Accurately weigh Cr with a molar ratio of 1:1.9 2 AlC powder and VC powder; Cr 2The purity of AlC powder is 98.9%, which was pre-sieved with 200 mesh; the purity of VC powder is 99.9%, and the particle size is 1.5μm. The weighed element powders were placed in an agate ball mill, and anhydrous ethanol was added to grind agate balls as wet grinding media. The ball milling was carried out at a speed of 160rpm for 3h. The mixed slurry was vacuum-rotated at 50℃ until it was completely dry to obtain a uniformly mixed mixed powder; the raw materials were pressed into discs by cold pressing at a pressure of about 380MPa for 2min using a tablet press, and placed in a conventional high-temperature tube furnace. The temperature was raised to the target sintering temperature of 1400℃ at a heating rate of 8℃ / min in a flowing argon atmosphere, and then kept warm for 2h; after the insulation, the temperature in the furnace was first reduced to 500℃ within 200min by program-controlled cooling, and then naturally cooled to room temperature to obtain the product.

[0042] The above contents are only for explaining the technical idea of ​​the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.

Claims

1. A method for preparing a Cr-V system out-of-plane ordered double transition metal MAX phase material, characterized in that: The following steps are involved: The Cr2AlC powder and the VC powder are mixed and ground to obtain a mixed slurry, and then dried to obtain a mixed powder, and the mixed powder is cold pressed and then calcined at a high temperature, and then cooled to room temperature to obtain a Cr-V system out-of-plane ordered double transition metal MAX phase material; The chemical formula of the Cr-V system out-of-plane ordered double transition metal MAX phase material is Cr2VAlC2 or Cr2V2AlC3.

2. The method for preparing the Cr-V system out-of-plane ordered double transition metal MAX phase material according to claim 1, characterized in that: The molar ratio of the Cr2AlC powder to the VC powder is 1:(0.9-2.0).

3. The method for preparing the Cr-V system out-of-plane ordered double transition metal MAX phase material according to claim 1, characterized in that: The particle size of the Cr2AlC powder is 100-300 meshes, and the purity is higher than 98%; the particle size of the VC powder is 1-10 μm, and the purity is higher than 99%.

4. The method for preparing the Cr-V system out-of-plane ordered double transition metal MAX phase material according to claim 1, characterized in that: The grinding method is ball milling, and agate balls and anhydrous ethanol are used as ball milling media during the grinding process; the rotation speed of the ball milling treatment is 120-200 r / min, and the time is 2-6h.

5. The method for preparing the Cr-V system out-of-plane ordered double transition metal MAX phase material according to claim 1, characterized in that: The drying conditions are: vacuum rotary evaporation at 40-60°C until completely dry.

6. The method for preparing the Cr-V system out-of-plane ordered double transition metal MAX phase material according to claim 1, characterized in that: The cold pressing forming conditions are: cold pressing for 1-3 minutes at a pressure of 200-500 MPa to form a round tablet.

7. The method for preparing the Cr-V system out-of-plane ordered double transition metal MAX phase material according to claim 1, characterized in that: The conditions for the temperature-raising calcination treatment are to raise the temperature to 1350-1550° C. at a heating rate of 5-10° C. / min in a flowing argon atmosphere and then keep the temperature for 1-3 hours.

8. The method for preparing the Cr-V system out-of-plane ordered double transition metal MAX phase material according to claim 1, characterized in that: The cooling conditions are: using program-controlled cooling to reduce the temperature to 400-600° C. within 200 minutes, and then naturally cooling to room temperature.

9. The Cr-V system out-of-plane ordered double transition metal MAX phase material prepared by the preparation method according to any one of claims 1 to 8, characterized in that: When the molar ratio of Cr2AlC powder to VC powder is 1:1.2 and the calcination temperature is 1500°C, the chemical formula of the Cr-V system out-of-plane ordered double transition metal MAX phase material is: Cr2VAlC2, and the mass fraction of the product is 74.9%.

10. The Cr-V system out-of-plane ordered double transition metal MAX phase material prepared by the preparation method according to any one of claims 1 to 8, characterized in that: When the molar ratio of Cr2AlC powder to VC powder is 1:1.9 and the calcination temperature is 1450°C, the chemical formula of the Cr-V system out-of-plane ordered double transition metal MAX phase material is: Cr2V2AlC3, and the mass fraction of the product is 90.1%.